(untitled) (South Asian Journal of Agriculture, 2022)
A study was conducted in the Agronomy Laboratory of Agrotechnology Discipline, Khulna University, Khulna, Bangladesh to find out the variations in grain characters of fifteen local rice cultivars collected from Khagrachari district, Bangladesh. Significant variations were observed in all of the investigated parameter. The highest and lowest length of grain was recorded in the cultivar Chonchonbini (7.1 mm) and Mashlajira (4.12 mm), respectively. Grain width of Badia (2.78 mm) was the highest and the lowest width was recorded in Mashlajira (2.13 mm). Grain thickness varied from 1.6 mm to 1.94 mm. The highest L/W ratio (3.11) was observed in Curi. Most of the variety showed medium grain shape. The highest alkali spreading score was found in Moisanguribini (6). All of the varieties showed soft gel consistency. Variation in grain characters observed among the local rice cultivars in the present study and these characters may be used as valuable resources for future breeding programs. South Asian J. Agric., 8(1&2): 51-56